Development and in vitro evaluation of liquid crystal-based polyherbal hair gels: physicochemical characterization, hair performance, and antioxidant assessment - David, Sheba R; Rajabalaya, Rajan; Mohamed Jefri , Umi Haida Nadia (Creative Pharma Assent, 2025)
Background: A liquid crystal (LC) based polyherbal hair gel was developed to enhance physicochemical stability and functional performance in topical hair care. The objective was to integrate herbal oils (flaxseed, coconut, and almond) and aqueous extracts (green tea, keratin hydrolysate, and pea peptide), known for their moisturizing, antioxidant, follicle-protective, and anti-frizz effects, into a stable gel matrix for scalp care and conditioning. Methodology: Ten formulations (F1–F10) incorporating flaxseed, coconut, and almond oils with green tea, marula extract (Sclerocarya birrea), keratin hydrolysate, and pea extract were prepared via coacervation, vortex mixing, and high-pressure homogenization. The gels were evaluated for their organoleptic properties, pH, spreadability, particle size (as determined by dynamic light scattering, DLS), polydispersity index (PDI), and zeta potential. Polarized Light Microscopy and FTIR characterized structural features. Functional performance was evaluated by in vitro studies on hair diameter and weight changes, as well as anti-frizz, anti-static, and antioxidant (DPPH) activities. Results and Discussion: Formulation F6 showed optimal nanometric characteristics (186.47 ± 1.90 nm, PDI 0.351 ± 0.01, zeta potential −35.9 mV), indicating stable colloidal dispersion. FTIR and microscopy confirmed molecular compatibility and mesophase birefringence. In vitro assessments revealed marked improvement in hair thickness for F6 and F9, with superior anti-frizz and anti-static performance for F4 and F9. Antioxidant activity was moderate compared to Trolox. F4 and F6 maintained stability over 28 days at different temperatures. Conclusion: F4 and F6 demonstrated superior in vitro performance and stability, suggesting promise as cosmeceutical hair care candidates. In vivo and clinical studies are required to confirm efficacy and long-term safety.